The impact of Confucian thoughts on Chinese women’s independence – focus on female university students - YUAN, YUAN (2017)
According to Oxford Advanced Learner’s Dictionary, an independent person should have or earn enough money and financially not rely on anybody. Additionally, they should be confident and are free to do whatever they want to do without seeking help from the others. Furthermore, Confucianism largely defined the mainstream discourse on gender in China since the Han dynasty, which has a far-researching impact on women’s independence in modern China. Confucian ideas advocate yin-yang theories suggesting that women are inferior to men and should depend on men. However, since open door policy published in 1978, owing to the influence of feminist thoughts, women began to accept education and participate in the workplace and then became more independent. Therefore, the aim of the paper is to explore the impact of Confucian ideas on Chinese women’s independence, focusing on Chinese female university students. 26 semi-structured interviews have been collected from the female students who are studying at the University of Nottingham, UK campus. Based on the literature review about Confucian and feminist theories, the paper addressed three research questions. Firstly, whether Confucian thoughts influence Chinese female university students’ independence? Secondly, how Confucian ideas impact Chinese female university students’ independence? Thirdly, what can be done with this phenomenon in contemporary China?